Prevalensi Ekspresi Epidermal Growth Factor Receptor (EGFR) pada Karsinoma Penis - Gede Khrisnanda Arya Dharma; Desak Putu Oki Lestari; Ni Wayan Armerinayanti; Ni Luh Putu Eka Kartika Sari (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2021)
Abstract[Prevalence of Epidermal Growth Factor Receptor (EGFR) Expression in Penis Carcinoma] Penile cancer is a malignancy in men, which is the highest in Bali compared to other regions in Indonesia. About 95% of malignancies in the penis are squamous cell carcinoma (SCC). The development of cancer therapy has now reached targeted therapy, while there has not been much research on penile cancer. Targeted therapy based on EGFR overexpression has developed and has been used as individual therapy, especially in lung cancer. This study aims to determine the expression of EGFR in the SCC of the penis. This study is a descriptive observational study to determine the prevalence of EGFR expression from immunohistochemical examination, tumor cells stained with intense brown color surrounding the entire tumor cell membrane. The results of the study of 141 samples of penile squamous cell carcinoma taken from biopsies, partial penectomy, and total penectomy. The prevalence of EGFR expression that was stained positively in penile cancer tumor cells was 8 cases (5.7%) with the highest age distribution in the age group 41-60 years as many as 66 cases (46.8%). Knowledge of EGFR overexpression in penile cancer can be used to reference anti-EGFR administration, especially in advanced penile cancer.